An STUDY OF THE RELATIONSHIP BETWEEN PSYCHOLOGICAL EMPOWERMENT AND THE LIFESTYLE OF WOMEN WORKING IN NORTH OF IRAN HOSPITALS - Bakhshi, Fataneh; Ramezani , Hedieh; Nezamdoust, Fatemeh; Kazemnejad Leili, Ehsan; Hossein zadeh, Maryam (Malaysian Journal of Public Health Medicine, 2021)
Lifestyle is a normal daily activity that people have accepted in their lives as pleasing. Empowerment, as the heart of health promotion, can be considered as a social action to increase behavioral dimensions of individual and society. The aim of this study was to determine the relationship between psychological empowerment and lifestyle of the women working in educational hospitals in North of Iran. This cross-sectional study was carried on 252 women with Spreitzer’s staff psychological empowerment scale and Health-promoting lifestyle profile II. The response rate was 91.3%. U-Mann Whitney, Kruskal Wallis, Spearman correlation and Logistic regression were used to determine the relationship between the variables. Age, marital status, shift work, socioeconomic status and BMI were significantly associated with health promoting behaviors. The mean score of psychological empowerment was 42.90 ± 9.15 and the mean score of health promoting behaviors was 142.83 ± 21.25. Work shift and age were also significantly related to employees' psychological empowerment. On the basis of regression analysis, the impact dimension was identified as the final determinant of health promoting behaviors. It is necessary to pay special attention to the psychological empowerment of employees, especially feeling efficacy at work and plan to enhance employees' health promoting behaviors.